The Political Ambitions of Serbian Patriarch Arsenije IV Jovanović Šakabenta - Kręzel, Piotr (Studia Ceranea, 2019)
Arsenije IV Jovanović Šakabenta (1698–1748) was one of the last leaders of the Peć Patriarchate. The period of his service coincided with the so-called Second Great Migration of the Serbs, i.e. the migration of portions of the Serbian society from Kosovo and Metohija to the southern territories of the Habsburg monarchy. This event majorly determined the actions of the patriarch at the end of the 1730s. The article outlines the political ambitions of Arsenije IV, which he tried to realize around that time. Particular focus is given to his vision of the Serbian community under the Habsburgs and to his efforts to retain the privileges which the Serbs had been granted by emperors Leopold I, Joseph I, and Charles VI. Additionally, the analysis covers the internal dynamics of the Serbian Orthodox Church in the territories of the Habsburg monarchy. The paper also touches upon the military issues and discusses the role of Serbian soldiers in the political plans of Arsenije IV Jovanović Šakabenta.